2020
DOI: 10.1016/j.autcon.2020.103251
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and interactive re-formulation of multi-objective optimization problems for conceptual architectural design exploration

Abstract: Simulation-Based Multi-Objective Optimization (SBMOO) methods are being increasingly used in conceptual architectural design. They mostly focus on the solving, rather than the re-formulation, of a Multi-Objective Optimization (MOO) problem. However, Optimization Problem Re-Formulation (Re-OPF) is necessary for treating ill-defined conceptual architectural design as an iterative exploration process. The paper proposes an innovative SBMOO method which builds in a dynamic and interactive Re-OPF phase. This Re-OPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 72 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…In this way, users can be engaged in the corresponding interaction design and contribute the corresponding design concept to the corresponding value experience. As a kind of qualitative evaluation and analysis, it is mainly about implementing user's experience analysis based on the constructive method [30,31]. In this paper, the effective evaluation based on the corresponding community tolerance method is implemented through the combination of different circles.…”
Section: User's Experience Evaluationmentioning
confidence: 99%
“…In this way, users can be engaged in the corresponding interaction design and contribute the corresponding design concept to the corresponding value experience. As a kind of qualitative evaluation and analysis, it is mainly about implementing user's experience analysis based on the constructive method [30,31]. In this paper, the effective evaluation based on the corresponding community tolerance method is implemented through the combination of different circles.…”
Section: User's Experience Evaluationmentioning
confidence: 99%
“…Moreover, a limited number of design exploration methodologies allow problem re-structuring. 4,8,22,38 In most cases, iteration happens between the two steps of form generation and evaluation (steps two and three). This shortcoming might be due to the assumption of unnecessary or unrealistic design restrictions or the inconvenience of pausing the automated design exploration procedure.…”
Section: State Of the Artmentioning
confidence: 99%
“…Several studies have demonstrated the importance of utilization of an appropriate design exploration methodology as well as decisions made during the conceptual phase of design [1][2][3] in which the designers uncover the design problem and solutions simultaneously [4][5][6] through an iterative process. 7 In the past decade, many computational design exploration methodologies have been developed to assist designers in generating and evaluating diverse solutions and making appropriate decisions.…”
Section: Introductionmentioning
confidence: 99%
“…When the iteration and automation are conducted to gather information about the building's performance, a huge amount of design feedback concerning its performance can be obtained to observe the design beyond the designer's imagination. Besides, multiobjective optimization (MOO) has recently become an approach in the built environment [14,15] to see the genetical trade-off between design objectives. One of the benefits of its use is that it reduces the negative impact on the environment where the building is constructed, for example, by lowering carbon emissions from energy consumption related to cooling and heating loads, comfort sensations that affect people's health [16], and urban heat island phenomena [17].…”
Section: Introductionmentioning
confidence: 99%